Usability of an electronic health record 6 months post go-live and its association with burnout, insomnia and turnover intention: a cross-sectional study in a hospital setting - Solveig Osborg Ose; Eivind Schjelderup Skarpsno; Arild Faxvaag; Lene Aasdahl; Ellen Marie Bardal; Hilde Brun Lauritzen; Signe Lohmann-Lafrenz; Sigmund Østgård Gismervik (BMJ Health & Care Informatics)
Objective The aim of this study was to assess how different groups of health professionals evaluated the usability of a new electronic health record (EHR) and to investigate the association between the usability and burnout, insomnia and turnover intention.Methods This cross-sectional study included 1424 health professionals who worked at a Norwegian University Hospital. The usability was measured with the System Usability Scale (SUS) 6 months after the previous electronic record was replaced with a more comprehensive, sector-wide, patient-centred EHR in 2022.Results The median SUS score was 25 (IQR 12.5–37.5) out of 100 and ranged from 15 (IQR 7.5–25.0) among medical doctors to 40 (IQR 27.6–55.0) among laboratory technicians. Nurses reported a score of 25 (IQR 12.5–40.0). In clinical contexts, the median SUS score ranged from 15 (IQR 10.0–30.0) within radiology to 27.5 (IQR 15.0–42.5) within internal medicine, whereas laboratory medicine reported a score of 37.5 (IQR 27.5–55.0). In multivariable analyses using health professionals in the highest quarter of the SUS as the reference, those in the lowest quarter were more likely to report burnout (OR 3.05, 95% CI 1.86 to 5.00), insomnia (OR 1.72, 95% CI 1.18 to 2.50) and turnover intention (OR 2.35, 95% CI 1.53 to 3.64).Conclusion Most health professionals across all occupational groups and clinical contexts reported low usability of a new EHR 6 months after go-live. Those who reported the lowest usability were more likely to report burnout, insomnia and turnover intention.